2012
DOI: 10.1007/s11239-012-0731-9
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of three prothrombotic polymorphisms among Palestinians: factor V G1691A, factor II G20210A and methylenetetrahydrofolate reductase C677T

Abstract: Factor V leiden G1691A/R506Q (FVL), prothrombin G20210A (FII) and methylenetetrahydrofolate reductase (MTHFR) C677T are related genetic risk factors for venous thromboembolism. Analysis for those mutations is increasingly being performed on patients exhibiting hypercoagulability. The objective of this study was to determine the prevalence of FVL, FII-G20210A and MTHFR-C677T polymorphisms and their coexistence among apparently healthy Palestinians. After institutional approval, 303 apparently healthy students f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
2
10
0
1
Order By: Relevance
“…These variants are also rare in African, Chinese, and American Indian populations (Herrmann et al, 2004;Jun et al, 2006). On the other hand, they are common in Arab countries, with frequencies as high as approximately 11% for FV G1691A and 5% for FII G20212A (P < 0.001), as observed by Hussein (2012) in a Palestinian population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These variants are also rare in African, Chinese, and American Indian populations (Herrmann et al, 2004;Jun et al, 2006). On the other hand, they are common in Arab countries, with frequencies as high as approximately 11% for FV G1691A and 5% for FII G20212A (P < 0.001), as observed by Hussein (2012) in a Palestinian population.…”
Section: Discussionmentioning
confidence: 90%
“…The high frequency of this polymorphism in the Asian countries Japan (40%) and Korea (44%) (Matsuo et al, 2004;Woo et al, 2009) were significantly different from the frequency found in this study (P = 0.003 and P = 0.011, respectively). Among the Arab countries, the frequency of this polymorphism ranges from 7 to 31% (Almawi et al, 2005;Hussein, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported a considerable difference between CVD patients and controls (12)(13)(14)(15), while others had no difference (16)(17)(18).…”
Section: Discussionmentioning
confidence: 89%
“…in Central Europe. Such a high prevalence of these SNPs cannot be ignored, especially when combined with other pro-thrombotic risk factors -oral contraceptives, immobility, pregnancy, cancer, age, and gender [55][56][57]. Therefore, we postulate that at least MTHFR C677T SNP should be included in genetic screening.…”
Section: Discussionmentioning
confidence: 99%